Research on Red/Near-Infrared Fluorescent Carbon Dots Based on Different Carbon Sources and Solvents: Fluorescence Mechanism and Biological Applications - Jun Song; Minghao Kang; Shujian Ji; Shuai Ye; Jiaqing Guo (Nanomaterials)
Fluorescent carbon dots, especially red/near-infrared-emitting CDs, are becoming increasingly important in the field of biomedicine. This article reviews the synthesis, fluorescence mechanisms, and biological applications of R/NIR-CDs, emphasizing the importance of carbon source and solvent selection in controlling their optical properties. The formation process of CDs is classified, and the fluorescence mechanisms of CDs are summarized, involving carbon core states, surface states, molecular states, and cross-linking enhanced emission effects. This article also highlights the applications of R/NIR-CDs in bioimaging, biosensing, phototherapy, and drug delivery. The final section discusses challenges and prospects.